Emergy perspective on the environmental and economic viability of a biomass-driven polygeneration system - Parviz Heydari Nasab; Ata Chitsaz; Hiva Rashidzadeh; Alireza Rostamzadeh Khosroshahi (Energy Conversion and Management: X)
Innovative methods have been increasingly adopted to evaluate industrial processes’ sustainability, environmental impact, and economic feasibility. Among these approaches, emergy analysis has emerged as a comprehensive tool. This study investigates a multiple system driven primarily by biomass gasification (using municipal solid waste) to generate power, heating, cooling, and freshwater. The gasification process incorporates a Brayton cycle, supplemented by natural gas to enhance the thermal value of the gas mixture. For cooling, a double-effect absorption chiller system utilizes the waste heat from the gas turbine, offering superior performance compared to single-effect systems. Additionally, a 24-stage Multi-Flash Distillation (MSF) unit produces freshwater, and the gasification unit’s dissipated heat is used for generated heating. The system’s performance was assessed using thermodynamic modeling in EES software, alongside an emergy analysis to determine economic and environmental parameters. Key metrics evaluated included the Emergy Yield Ratio (EYR), Emergy Investment Ratio (EIR), Environmental Loading Ratio (ELR), renewability, and Emergy Sustainability Index (ESI). Critical variables such as Gas Flow Rate (GMR), Equivalence Ratio (ER), Gasification Temperature (Tgh), Combustion Chamber Temperature (Tcc), and Combustion Chamber Pressure (Pcc) were examined. The subsystems were individually validated based on credible sources, and finally, the system was evaluated. Results indicated that the total emergy value of the system was 2.03E + 20, with maximum sustainability indices of 8.5, 6.81, 6.2, 6.13, and 6.6 across the system’s variables, respectively. The net power output reached 18.756 MW. However, as variable values increased, system sustainability decreased while net power output improved. This study demonstrates the potential of biomass-based systems for sustainable emergy solutions while highlighting the trade-offs between efficiency and environmental impact.